Evaluating efficiency in the Brazilian trucking industry - Peter Fernandes Wanke (Production)
The purpose of this study is to investigate the issue of efficiency in the Brazilian motor carrier industry using both DEA (Data Envelopment Analysis) and SFA (Stochastic Frontier Analysis) in a complimentary fashion. The study is based on secondary data collected from Transporte Moderno/Maiores e Melhores, a specialized magazine that annually reports statistics on the largest Brazilian trucking companies. Results corroborate not only that increasing returns to scale prevail within this industry, but also provide support for a moderate impact of economies of scope on efficiency levels. Implications in terms of mergers and acquisitions and the impact of cargo diversity and the geographical scope of the operation on virtual efficiency levels are also addressed.